Structural evolution of ferromagnetic ³He multilayers adsorbed on exfoliated graphite - Antsygina, T.N.; Chishko, K.A. (Физика низких температур, 2013)
On the basis of our theoretical results describing two-dimensional spin-1/2 Heisenberg model in an external magnetic field we analyze and interpret known from literature experimental data on magnetization of pure ³He monolayers on graphite at ferromagnetic coverages. We clarify the experimentally observed temperature dependences for 2D ³He magnetization under magnetic fields of different magnitude. The cluster size effect in the temperature dependence of the magnetization is studied. We interpret the spin exchange variation in 2D multilayered ³He system during successive promotion of the second, third and fourth layers over first paramagnetic layer strongly coupled with graphite substrate.